Analisis Strategi Pembelajaran Berdiferensiasi terhadap Hasil Belajar Peserta Didik: Systematic Literature Review - Rachmadhani, Santa Aulia Devi; Kamalia, Putri Ulfa (STAI Auliaurrasyidin Tembilahan, 2023)
Educators often have difficulty delivering effective learning when they have to deal with the diversity of learners in one class, resulting in suboptimal learner learning outcomes. The purpose of this study was to determine the effect of differentiated learning strategies on student learning outcomes through a literature review. The research method used is systematic literature review. Data was collected through articles and scientific papers using inclusion and exclusion criteria. Articles focused on differentiated learning strategies and their impact on learning outcomes at secondary and tertiary levels. Articles were selected from 2015 to 2023 using Sinta, Google Scholar, and Scopus. Through identification, screening, and eligibility of articles based on criteria, 16 articles were obtained that met the objectives of the literature review. The analysis showed that 94% of the articles indicated that differentiated learning strategies positively influence learning outcomes. However, it cannot be ignored that 6% of the articles showed that there are situations where differentiated learning strategies do not have a significant impact on learning outcomes in a positive way.